Serum Renalase Level as A Marker of Activity and Severity in Lupus Nephritis Cases - Gazar, Yasser (European Journal of Applied Sciences, 2021)
- Introduction: Lupus nephritis (LN) is a substantial risk factor for death and morbidity in patients with Systemic Lupus Erythematosus (SLE) (SLE). Despite excellent immunosuppressive therapy, it nevertheless leads to a disproportionate percentage of persons developing chronic kidney disease (CKD) or end-stage renal disease (ESRD). Renalase is a distinctive cytokine-like protein generated by the kidneys that promote cell survival. It has been recently linked to the etiology of LN and may be an ideal candidate as a sensitive biomarker for flare-ups and LN remission. -Aim of the work: The purpose of this study was to evaluate the utility of human serum renalase as a biomarker for assessing disease activity and severity in SLE, as well as to evaluate if it can be used as a sensitive biomarker in this capacity. -Methods: This study consists of around 23 healthy controls and 46 individuals with LN. These participants were separated into two equal groups according to disease activity as determined by the SLEDAI (SLE Disease Activity Index): 23 cases with LN who had disease activity and 23 cases who did not. The concentration of human serum Renalase (RNLS) was evaluated using a very sensitive commercial enzyme immunoassay that captures renalase from serum using (RNLS) antibody. - Results: Renalase concentrations were significantly greater in LN cases than in healthy controls (P-value <0.001). Additionally, cases with active LN exhibited significantly greater serum renalase concentrations than those with inactive LN (P-value <0.005). Serum renalase concentrations were positively connected with 24-h urine protein excretion, SLEDAI, ESR, CRP, and ds-DNA but were negatively related to serum C3 and the class (particularly in the proliferative type) (Class III, IV, more than class V). -Conclusion: Serum renalase levels were associated with disease symptoms in LN and may serve as a biomarker for disease activity in LN.